Capacity Strengthening training: ‘Fundamentals of Input-Output Analysis and Social Accounting Matrix (SAM) based Multiplier Modeling for Economy Wide Impact Assessment’ at RPCAU, Pusa, Samastipur, Bihar, India - CGIAR Initiative on National Policies and Strategies (CGIAR, 2023)
Agricultural Economics Research Association organized a capacity strengthening training on “Fundamentals of Input-Output Analysis and Social Accounting Matrix (SAM) based Multiplier Modeling for Economy Wide Impact Assessment” on 6th December 2023 in RPCAU (Pusa), Samastipur, Bihar. Dr. Barun Deb Pal, and Mr. Manmeet Singh Ajmani from IFPRI conducted the training.